The Influence of Local Government Size, Leverage, and Audit Opinion on Transparency of Regional Financial Reports with Internet Financial Reporting as an Intervening Variable : (Case Study of District/City Governments in Indonesia 2018-2020) - Riska Puji Astuti; Imanda Firmantyas Putri Pertiwi (Accounting and Finance Studies, 2022)
The purpose of this study was to determine the effect of local government size, leverage, and audit opinion on the transparency of regional financial reports using internet financial reporting as an intervening variable. This study uses a quantitative method with a sample of 35 districts/cities in Indonesia in 2018-2020. The data in this study are secondary data obtained from the official website of the district/city government in Indonesia. Analysis of Path Analysis test data with the help of SPSS version 26. The results of this study conclude that local government size and audit opinion have no effect on regional financial transparency. Leverage affects regional financial transparency. Local government size, leverage, and audit opinion have no effect on internet financial reporting. Internet financial reporting is not able to mediate all independent variables on regional financial transparency.